Pauses in Striatal Cholinergic Interneurons: What is Revealed by Their Common Themes and Variations? - Zhang, Yan-Feng; Cragg, Stephanie J. (Frontiers in Systems Neuroscience, 2017)
Striatal cholinergic interneurons, the so-called tonically active neuron (TANs), pause their firing in response to sensory cues and rewards during classical conditioning and instrumental tasks. The respective pause responses observed can demonstrate many commonalities, such as constant latency and duration, synchronous occurrence in a population of cells, and coincidence with phasic activities of midbrain dopamine neurons that signal reward predictions and errors. Pauses can however also show divergent properties. Pause latencies and durations can differ in a given TAN between appetitive versus aversive outcomes in classical conditioning, initial excitation can be present or absent, and a second pause can variably follow a rebound. Despite more than 20 years of study, the functions of these pause responses are still elusive. Our understanding of pause function is hindered by an incomplete understanding of how pauses are generated. In this mini-review, we compare pause types, as well as current key hypotheses for inputs underlying pauses that include dopamine-induced inhibition through D2-receptors, a GABA input from ventral tegmental area, and a prolonged afterhyperpolarization induced by excitatory input from the cortex or from the thalamus. We review how each of these mechanisms alone explains some but not all aspects of pause responses. These mechanisms might need to operate in specific but variable sets of sequences to generate a full range of pause responses. Alternatively, these mechanisms might operate in conjunction with an underlying control mechanism within cholinergic interneurons which could potentially provide a framework to generate the commonality and the divergence seen amongst pause responses.